Low-intensity pulsed ultrasound regulates osteoblast-osteoclast crosstalk via EphrinB2/EphB4 signaling for orthodontic alveolar bone remodeling - Zhou, Jie; Zhu, Yanlin; Ai, Dongqing; Zhou, Mengjiao; Li, Han; Fu, Yiru; Song, Jinlin (Frontiers in Bioengineering and Biotechnology, 2023)
Background: The limited regenerative potential of periodontal tissue remains a challenge in orthodontic treatment, especially with respect to alveolar bone remodeling. The dynamic balance between the bone formation of osteoblasts and the bone resorption of osteoclasts controls bone homeostasis. The osteogenic effect of low-intensity pulsed ultrasound (LIPUS) is widely accepted, so LIPUS is expected to be a promising method for alveolar bone regeneration. Osteogenesis is regulated by the acoustic mechanical effect of LIPUS, while the cellular perception, transduction mode and response regulation mechanism of LIPUS stimuli are still unclear. This study aimed to explore the effects of LIPUS on osteogenesis by osteoblast-osteoclast crosstalk and the underlying regulation mechanism. Methods: The effects of LIPUS on orthodontic tooth movement (OTM) and alveolar bone remodeling were investigated via rat model by histomorphological analysis. Mouse bone marrow mesenchymal stem cells (BMSCs) and bone marrow monocytes (BMMs) were purified and used as BMSC-derived osteoblasts and BMM-derived osteoclasts, respectively. The osteoblast-osteoclast co-culture system was used to evaluate the effect of LIPUS on cell differentiation and intercellular crosstalk by Alkaline phosphatase (ALP), Alizarin Red S (ARS), tartrate-resistant acid phosphatase (TRAP) staining, real-time quantitative PCR, western blotting and immunofluorescence. Results: LIPUS was found to improve OTM and alveolar bone remodeling in vivo, promote differentiation and EphB4 expression in BMSC-derived osteoblasts in vitro, particularly when cells were directly co-cultured with BMM-derived osteoclasts. LIPUS enhanced EphrinB2/EphB4 interaction between osteoblasts and osteoclasts in alveolar bone, activated the EphB4 receptor on osteoblasts membrane, transduced LIPUS-related mechanical signals to the intracellular cytoskeleton, and gave rise to the nuclear translocation of YAP in Hippo signaling pathway, thus regulating cell migration and osteogenic differentiation. Conclusions: This study shows that LIPUS modulates bone homeostasis by osteoblast-osteoclast crosstalk via EphrinB2/EphB4 signaling, which benefits the balance between OTM and alveolar bone remodeling.